2012
DOI: 10.1016/j.immuni.2012.04.015
|View full text |Cite
|
Sign up to set email alerts
|

TBK-1 Promotes Autophagy-Mediated Antimicrobial Defense by Controlling Autophagosome Maturation

Abstract: Summary Autophagy is a fundamental biological process of the eukaryotic cell contributing to diverse cellular and physiological functions including cell-autonomous defense against intracellular pathogens. Here we screened the Rab family of membrane trafficking regulators for effects on autophagic elimination of Mycobacterium tuberculosis var. bovis BCG and found that Rab8b and its downstream interacting partner, innate immunity regulator TBK-1, are required for autophagic elimination of mycobacteria in macroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
540
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 567 publications
(574 citation statements)
references
References 50 publications
20
540
2
Order By: Relevance
“…Typhimurium by controlling autophagy. Consistent with TBK1 controlling anti‐bacterial autophagy is the enzyme's ability to phosphorylate functionally important sites in cargo receptors, namely the LC3‐interacting region (LIR) of optineurin (Wild et al , 2011) and the ubiquitin‐binding site of p62 (Pilli et al , 2012), thereby enhancing their affinity for LC3 and ubiquitin, respectively. While the spatial and temporal control of the tethering function of cargo receptors appears as an important contribution of TBK1 to anti‐bacterial autophagy, we found that in Tbk1 −/− MEFs, LC3 is still recruited to S .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Typhimurium by controlling autophagy. Consistent with TBK1 controlling anti‐bacterial autophagy is the enzyme's ability to phosphorylate functionally important sites in cargo receptors, namely the LC3‐interacting region (LIR) of optineurin (Wild et al , 2011) and the ubiquitin‐binding site of p62 (Pilli et al , 2012), thereby enhancing their affinity for LC3 and ubiquitin, respectively. While the spatial and temporal control of the tethering function of cargo receptors appears as an important contribution of TBK1 to anti‐bacterial autophagy, we found that in Tbk1 −/− MEFs, LC3 is still recruited to S .…”
Section: Discussionmentioning
confidence: 99%
“…TBK1 accumulates in the vicinity of cytosol‐exposed bacteria together with its adaptor proteins Nap1, Sintbad, and their binding partner NDP52 (Fujita et al , 2003; Ryzhakov & Randow, 2007; Thurston et al , 2009; Verlhac et al , 2015). TBK1 also associates with optineurin and it has been reported to phosphorylate both optineurin and p62, thereby enhancing their affinity for LC3B and ubiquitin, respectively (Morton et al , 2008; Wild et al , 2011; Pilli et al , 2012; Heo et al , 2015; Richter et al , 2016). While these findings imply that TBK1 strengthens the tethering function of cargo receptors, TBK1 has also been suggested to promote autophagosome maturation (Pilli et al , 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…43 ICP34.5 interaction with TBK1 inhibits the induction of antiviral signaling exerted by TBK1, facilitating viral replication and neuroinvasion. 43,44 Given that TBK1 is a necessary factor for autophagic maturation, which can phosphorylate the autophagic receptors SQSTM1/p62 (sequestosome 1) and OPTN (optineurin) to regulate cargo recruitment into phagophores for degradation, 45,46 direct inhibition of TBK1 may represent an additional way that ICP34.5 suppresses autophagic function, yet this conclusion awaits further investigation. In addition to ICP34.5, tegument protein Us11 has also been implicated in the regulation of the autophagy pathway.…”
Section: Hsv-1 Inhibition Of Cellular Autophagymentioning
confidence: 99%
“…The interaction between TBK1 and OPTN1 is a key factor in autophagy and inflammation (Maruyama et al, 2010;Maruyama and Kawakami, 2013;Thomas et al, 2013;Kachaner et al, 2012). TBK1 enhances the autophagic turnover of bacteria-bound ubiquitylated proteins (Wild et al, 2011;Gleason et al, 2011), through the phosphorylation of OPTN and SQSTM1 (Morton et al, 2008;Pilli et al, 2012) and promoting the interaction of OPTN with LC3. TBK1 co-localization with OPTN and SQSTM1 within autophagosomes, even in cells carrying SOD1, TARDBP and FUS mutation, suggests a still undisclosed role of these proteins in aggregate formation in ALS (Keller et al, 2012).…”
Section: Accumulation Of Als Pathogenetic Proteins and Autophagymentioning
confidence: 99%